Wprowadzanie definicji legalnych w prawie podatkowym — zagadnienia wyjściowe - Borszowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article concerns one of the most important issues for the regulation of tax law, namely the introduction of legal definitions. Introducing legal definitions into the tax law is one of the most difficult problems of the doctrine and practice of tax law. The author formulates the thesis that the introduction of these definitions in the area of tax law should satisf the specific determinants. The state of the current legal regulation indicates that these determinants are not recognized and selected determinants are abused. According to the author, errors in this case made by the legislator cause negative consequences not only for the tax law, but also for the legal system. This involves the abuse of the autonomy of tax law.The author formulates the determinants of introducing these definitions in the area of tax law. As for the determinants established outside the control principles of legislative techniques, as well as the determinants established in the area of rules of legislative technique. The author also establishes the determinants of introducing legal definitions resulting from the postulate to reduce the amount of blurred terms.According to the author, adherence to these determinants contributes not only to limiting the amount of legal definitions, but also to improving the quality of tax law. Creating too many legal definitions causes the opposite effect than expected.
Keywords: definicje prawne; prawo podatkowe; autonomia prawa podatkowego; uwarunkowania wprowadzenia definicji prawnych